Dual-Polarity Early Carboniferous Remagnetization of the Fisset Brook Formation, Cape Breton Island, Nova Scotia - Johnson, Rex J. E.; Van der Voo, Rob (Geophysical Journal International, 1989)
Red siltstones and volcanic flows of the Fisset Brook Formation of Cape Breton Island, Nova Scotia, were folded or tilted in two phases, one of Late Tournaisian and the other of Mid-Namurian age. Upon thermal demagnetization, both rock types yield three components of magnetization, herein denoted as L, I and H. the L component has low unblocking temperatures and a direction conforming to that of the present-day geomagnetic field. L is inferred to be of recent origin. the intermediate I component, carried by haematite, is of synfolding origin. Directions could be obtained through vector subtraction for the demagnetization interval of 300–550 °C, and yield a mean of D / I = 160°/+38° ( k = 90.8, α 95 = 5.1°), after 39 per cent of the tilt correction is applied. the H component has even higher unblocking temperatures, which overlap to a large degree with those of the I component, but analysis of intersecting great circles appears to yield a best-fit direction for H which is nearly antipodal to that of the I component. H is also synfolding, and yields a mean direction of D / I = 342°/−38° ( k = 120.9, α 95 = 6.9°) after 60 per cent of tilt correction. Both components are interpreted as secondary chemical remanent magnetizations of Late Tournaisian to Early Namurian age. A comparison of all available Carboniferous results from the craton and the northern Appalachians indicates that palaeolatitudes for Nova Scotia changed from about 20°S to about 10°S in the interval between the Early and Late Namurian and that they changed again from about 10°S to 0° between the Late Namurian and the Stephanian. Declinations show good agreement between Newfoundland, Nova Scotia, New Brunswick and the craton, with the exception of the Meguma terrain, which underwent a counterclockwise rotation with respect to the mainland in the Late Carboniferous, as noted previously by Spariosu, Kent & Keppie (1984).